KEJUTAN BUDAYA TOKOH UTAMA SABINE DALAM DSCHUNGELKIND KARYA SABINE KUEGLER - Tanjung, Sufriati (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2011)
This study aims to describe culture shocks experienced by Sabine in terms of forms, causes, and solutions. The data were collected from Dschungelkind by Sabine Kuegler through reading and recording and were categorized, analyzed, and interpreted. The findings are as follows. First, Sabine experiences culture shocks related to daily life. Second, they occur because of her ignorance of daily life customs in a new place, her inability in interaction involving covert cultural aspects, and her ethnocentricity in interaction. Third, she comes from a family full of affection so that she is strong, honest, and accustomed to saying prayers. This enables her to deal with culture shocks. Besides, her close friends and relatives help her solve the problems.Keywords: cultural